Methods in mind - Senior, Carl; Russell, Tamara; Gazzaniga, Michael S. (Cognitive neuroscience., 2006)
Experts discuss the wide variety of investigative tools available to cognitive neuroscience, including transcranial magnetic stimulation, neuroscience computation, fMRI, imaging genetics, and neuropharmacology, with particular emphasis on convergence of t.